Removal of Heavy Metal Ions (Pb2+, Co2+, and Cd2+) by Activated Carbon from Cypress Fruit: An Investigation of Kinetics, Thermodynamics, and Isotherms - Alaa M. Al-Ma’abreh; Dareen A. Hmedat; Gada Edris; Mariam A. Hamed (Journal of Chemistry)
In this study, activated carbon cloth (ACC) derived from cypress fruit was employed to investigate the adsorption of Pb2+, Cd2+, and Co2+ from synthetic aqueous systems. The correlation between adsorption features (pH, adsorbent dosage, temperature, initial ion concentration, and contact time) and adsorbent removal efficiency was investigated. Analysis by FT-IR, SEM, and EDS was employed to confirm the adsorption of metal ions onto the ACC. Results revealed the best adsorption efficiencies for heavy metal ions were attained at pH = 7, 11, 6; the adsorbent dosage of 0.06, 0.08, and 0.04 g for Pb2+, Cd2+, and Co2+, respectively; the ion initial concentration of 50 mg·L−1 for Pb2+ and 70 mg·L−1 for both Co2+ and Cd2+; and contact time of 90 minutes for both Pb2+ and Co2+ and 120 minutes for Cd2+. Kinetic studies exposed the second-order adsorption of all aforementioned heavy metal ions. Additionally, the equilibrium data were fitted by Langmuir and Freundlich’s isotherms, while the former performed better than the latter. The maximum adsorption capacity values for Pb2+, Co2+, and Cd2+ were attained to 81.87, 55.30, and 117.3 mg·g−1, respectively. Considering the thermodynamic data, the studied processes were exothermic and spontaneous.